PERANAN POLA KEMITRAAN PETERNAKAN AYAM BROILER PADA PT.GUP (GEMILANG UNGGAS PRIMA) TERHADAP PENDAPATAN PETERNAK DI KECAMATAN TAMBANG KABUPATEN KAMPAR - Sari, Rena Purnama; Nas, Sakdanur; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Broiler farm is a business that can be relied upon to meet the needs of family life or a business that can be managed commercially. Initially the farm business is shaped farms. Because of the weakness in the system of capital, technology, and marketing then formed a business partnership between breeder farms with large employers. The purpose of this study was to determine the pattern of partnerships run by PT GUP (Gemilang Unggas Prima) and also the role of partnerships to income farmers in sub Tambang Kampar district. The population in this study were 32 farmers, samples are used mainly for 14 people with purposive sampling method. Data collection techniques are observation, interviews, documentation. Data analysis technique used is descriptive analysis of qualitative and quantitative descriptive. Qualitative descriptive analysis is used to describe patterns and the role of partnerships run by PT.GUP. quantitative descriptive analysis is used to analyze the business income of livestock before and after participating in the partnership. The results of this research is a partnership run by PT.GUP is a pattern where the company Inti Plasma GUP as Plasma Core assist in providing a means of animal production (sapronak), to provide technical guidance and help marketing the product. While farmers as the plasma form stable supply of land, labor and carry out production activities in accordance with an agreement with the Core. The role of the partnership has no effect on operating income of farmers, where the average income is smaller than the partners breeders independent farmers, but the partnership provides benefits to farmers including sustaining capital, capital assistance, technical guidance and maintenance of the marketing of livestock production.Keywords : Pattern partnership , Farm chicken broiler , breeder revenue